Robert Kennedy : brother protector - Hilty, James W. (Temple University Press, 1997)
For most of his life, Robert Kennedy stood in the shadow cast by his older brother, John; only after President Kennedy's assassination did the public gain a complete sense of Robert (""Bobby,"" we called him) as a committed advocate for social justice and a savvy politician in his own right. In this comprehensive biography, James W. Hilty offers a detailed and nuanced account of how Robert was transformed from a seemingly unpromising youngster, unlikely to match the accomplishments of his older brothers, to the forceful man who ran ""the family business,"" orchestrating the Kennedy quest.